Regulating Buy Now Pay Later (BNPL) in Asean: a Comparative Analysis on Regulatory Challenges and Opportunities - Luci Irawati; Muhammad Zilal Hamzah; Eleonora Sofilda (International Journal of Economics, Management and Accounting, 2024)
This study provides a comparative analysis of the regulatory frameworks governing Buy Now Pay Later (BNPL) services across ten ASEAN countries: Indonesia, Malaysia, Singapore, Thailand, the Philippines, Laos, Brunei Darussalam, Vietnam, Myanmar, and Cambodia. As BNPL services rapidly expand throughout the region, understanding the diverse regulatory landscapes and their implications becomes increasingly critical for fostering financial stability, consumer protection, and innovation in the digital financial ecosystem. Utilizing a literature review methodology, the research examines existing regulations, legal frameworks, and market trends, assessing their impact on financial stability, consumer protection, and fintech innovation. Singapore is identified as the leader in regulatory practices, effectively balancing fintech innovation with stringent consumer protection. Indonesia and Malaysia emphasize financial inclusion and systemic risk management, with Indonesia's framework focusing on transparency and financial literacy. Thailand and the Philippines are refining their frameworks, while Myanmar, Laos, Brunei, Vietnam and Cambodia are still developing their regulatory approaches. BNPL services, driven by growing e-commerce and fintech ecosystems, offer significant opportunities for financial inclusion but also pose challenges related to over-indebtedness, credit risk, and data protection. The analysis emphasizes that while BNPL presents significant opportunities for financial inclusion and fintech innovation, effective regulation is critical to ensuring sustainable growth and protecting consumers from debt traps and financial instability.